Palladium-induced transformation of nematic liquid crystals to robust metallogel comprising self-assembled nanowires. Issue 84 (3rd October 2019) - Maiti, Bappa; Bhattacharjee, Subham; Bhattacharya, Santanu
Abstract : Transformation of nematic liquid crystals to metallogels. Abstract : The formation of a nematic liquid-crystalline phase in the bulk along with gelation of a novel asymmetric bolaamphiphilic NDI scaffold has been demonstrated. Further, a discrete metal NDI complex that is capable of forming a robust metallogel through wrapping of the NDI core with the oxyethylene chains of the neighboring molecules has been synthesized.